Ketorolac After Free Tissue Transfer: A Comparative Effectiveness Study. (June 2014) - Schleiffarth, J. Robert; Bayon, Rodrigo; Chang, Kristi E.; Van Daele, Douglas J.; Pagedar, Nitin A.
Objective: We sought to compare postoperative pain and complications in patients undergoing free tissue transfer for reconstruction of head and neck defects with and without ketorolac. Methods: In this retrospective cohort study, we identified patients who underwent head and neck free tissue transfer procedures at the University of Iowa between July 2010 and December 2012. A subset of patients received ketorolac as an anti-platelet agent. Main outcome measures include postoperative analgesic use, pain scores, and bleeding complications. Results: We identified 138 free tissue transfers, with 42 procedures in the ketorolac cohort. In the first 7 postoperative days, patients in the ketorolac and non-ketorolac cohorts received equivalent narcotic doses (morphine equivalents, 48.9 mg/day vs 46.6 mg/day, P = .72). The ketorolac group reported higher mean pain scores (3.1 vs 2.4, P = .004). Ketorolac use was not associated with need for transfusion ( P = .86) or number of days with neck drains ( P = .79). Conclusion: Ketorolac did not demonstrate a significant analgesic effect in this group of patients in terms of pain scores and opioid requirements. However, there also was no evidence to suggest a higher likelihood of bleeding complications. Ketorolac may be safely used as an anti-platelet agent, with narcotic requirements unchanged.